2004
DOI: 10.1111/j.1399-543x.2004.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Ponderal gain, waist-to-hip ratio, and pubertal development in girls with type-1 diabetes mellitus

Abstract: Pubertal development in girls with T1DM occurred earlier than described in historical cohorts, but a later onset of menarche and final stages of breast development were observed. The increase in BMI-SDS and the stability of WHR in girls with T1DM during puberty suggest that this period may be critical for determining later weight gain and body composition in adult women with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
6
38
0
7
Order By: Relevance
“…We found that pubertal development in the obese adolescent girls occurred earlier than that in the adolescent girls with T1DM. This finding is in agreement with what has been reported by others in obese (34) and adolescent girls with T1DM (35,36,37,38).…”
Section: Discussionsupporting
confidence: 83%
“…We found that pubertal development in the obese adolescent girls occurred earlier than that in the adolescent girls with T1DM. This finding is in agreement with what has been reported by others in obese (34) and adolescent girls with T1DM (35,36,37,38).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, we observed that T1D girls exhibit a delay in the attainment of breast Tanner stages 3 and 4 [2]. The German study documented a delay of 4 months for Tanner stage 3 only [1, 2], and pubic hair Tanner stages 3 and 4 were delayed in T1D girls from both studies.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 67%
“…In view of the limitations in the available literature, we studied a large group of T1D girls and a concomitant control group, carefully matched both by ethnicity and socio-economic status [2]. We evaluated 100 T1D and 576 healthy girls in a cross-sectional study, and observed a similar age of onset of thelarche in both groups, which occurred one and a half years earlier than historical controls.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that fat tissue is an endocrine gland that secretes numerous adipocytokines, which are involved in regulating insulin sensitivity. Since the secretion of these hormones is influenced by fat mass and since girls with DM1 gain excessive weight and fat mass during puberty [5,6,7], the involvement of these hormones in the pubertal process may be critical for understanding the endocrine abnormalities observed in DM1 girls during this period.…”
Section: Introductionmentioning
confidence: 99%